LANGUAGE VARIETIES IN AL-AMANAH ISLAMIC MODERN COLLEGE: SEEN FROM LANGUAGE IN CONTACT - ULUM, MIFTAKHUL (Language Horizon: Journal of Language Studies, 2014)
LANGUAGE VARIETIES IN AL-AMANAH ISLAMIC MODERN COLLEGE: SEEN FROM LANGUAGE IN CONTACT Miftakhul Ulum The State University of Surabaya Faculty of Languages and Arts Discipline of Language Literature miftahulum89@yahoo.co.id Slamet Setiawan The State University of Surabaya Faculty of Languages and Arts Discipline of Language Literature s.setiawan@unesa.ac.id ABSTRACT This study is about language varieties and the results of language in contact. This is conducted because of the existence of language varieties in Al-Amanah Islamic Modern College. The language varieties are English influenced by Surabaya and Sidoarjo Javanese. Besides, the purposes of this study are to know how the phenomena of language varieties existing in Al-Amanah Islamic modern college including the (1) forms, (2) the factors and (3) the acceptability in English Speakers’ Societies. It is conducted by using Weinrich’s interlanguage theory approach (1972). The design of this study is descriptive qualitative method and analyzed by using Miles’ and Huberman’s model including data reduction, data display, and conclusion and verification. This study say that the language varieties are English influenced by Surabaya and Sidoarjo dialect and accent and in the forms of interferences, integration and convergence, code-switching and code-mixing, pidgin, and Creole. Meanwhile, there are two factors caused the existence of these language varieties. They are internal factors including multilingualism which Javanese as the majority language, and lack of vocabularies and grammar knowledge. Secondly, the external factors include the existence of cultural heritage of the seniors, habit in the use of these language varieties, and the Islamic College rules. Seen from their acceptability, this study says that these language varieties are unacceptable. In summary, language varieties happening in Al-Amanah Islamic Modern College is English influenced by Surabaya and Sidoarjo Javanese. The factors are divided into internal and external, and these language varieties are unacceptable in language speakers’ society. Keywords: language variety, Surabaya and Sidoarjo Javanese, language contact INTRODUCTION Each country has a specific language. Indonesia, for example, is a multilingual country. In 2012 Indonesia has 546 languages.1 It is assumed that the number of languages in Indonesia will increase in each year. East Java, Indonesia, has 4 languages with different dialects and accents.2 They are Javanese, Madurese, Osing, and Indonesian. Therefore, if a country has a lot of languages, it can be ensured that language varieties exist. www.kompas.com Dinas kominfo prov. Jatim, 2012 Language variety is a variation of using a language. Language varieties include such as dialect, accent, style, and so on. Language varieties often appear in bilingual speakers or multilingual ones. For instance, it is in Al-Amanah Islamic Modern College, Krian. The students must speak in more than two languages. They are Arabic, English and refined Javanese (Jawa krama). However, they often produce a “foreign language” which is influenced by the language contact while speaking. Multilingual community means that the community has more than two languages to speak and to communicate each other. Holmes (2000: 73) defines that multilingual is an ability to use more than two languages in communication for certain purpose. Why should it be more than two languages? The answer is that each of them has their own terms. For people or groups who are able to use only one language, they are called as monolingual. García and Colin (1995:41)199541 define that “monolingual is a person ‘who’ knows only one language, whatever that means”. Meanwhile, for people or groups who are able to use two languages, they are named as bilingual. Therefore, seen from the number of the languages used, linguists categorized them into three parts. They are monolingual, bilingual, and multilingual. Concerning with the multilingual situation, it can be ensured that there will be language contact appearing among them. Language contact is a phenomenon influencing one language to another. Thomason (2001: 1) also defines language contact as the influence of one language to another, directly or indirectly, in the same place at the same time, so that it can change the language which is used by the speaker. Language contact can be found easily when there are at least two people with different languages talking each other. For instance, the one speaks English and the other speaks Javanese. Sooner or later their languages will influence each other. Commonly, one of the language contact results is integrations (Chaer and Agustina, 2010: 84). Then, The Javanese will get new words from the English, and so does the English. Al-Amanah Islamic Modern College is an Islamic modern college located in the Kewangen, Junwangi, Krian, Sidoarjo. Javanese or Indonesian usually calls this institution as pondok pesantren. Pondok pesantren is an institution built by an Islamic priest (kiyai). This institution specifically teaches the students a religious education. The students who study are called as santri. The term santri is only used in Indonesia because Indonesia is the first country which uses living system in education, especially in Java Island (Moesa, 2007:95). In Al-Amanah Islamic Modern College, there is a kind of language varieties. It is influenced by a contact between a foreign language and regional language. The foreign language focused here is English. Meanwhile, the regional language is Javanese with Surabaya and Sidoarjo dialect and accent. It makes the influenced foreign language to be very different from the real ones. In their daily conversation, the students usually produce some new words which are not available in its foreign languages vocabularies. The examples of words that usually they produce are “This is lo very buuwwig e, come here aaa!(instead of this is very big, and come here!)”, and so on. Why should the foreign languages be influenced by Surabaya and Sidorajo? The answer is that most of the students are from Surabaya and Sidoarjo. Rachmawati (2007), the student of State University of Surabaya, ever conducted a study under the title “The Interference of Bahasa Indonesia to The Production of English Sounds Made by The Third Grade Students of Junior High School in Al-Furqon Muslim Boarding School”. It emphasized on the English words formation interfered by bahasa Indonesia and English seen from phonological point of view. This study was done to know the interference of bahasa Indonesia to the production of English sounds made by the third grade students of junior high school in Al-Furqon Muslim Boarding School. The data related to interference was obtained through oral reading passages process conducted in the classroom. The conclusion of this study was there were some difficult consonants to pronounce. They were /v/, /?/, /ð/, and /d?/ caused by the absence of those sounds in bahasa Indonesia. Besides, Bhela (1999), the student of Flinders University School of Education also conducted study under the title “Native Language Interference in Learning a Second Language: Exploratory Case Studies of Native Language Interference with Target Language Usage”. It emphasized on the forms of the second language structures in the written form done by Spanish, a Vietnamese, a Cambodian, and an Italian. It means that the study was focused on the structures of the second language (L2) learners sometimes constructed based on their first one (L1) through written task. This study was conducted to know the effect of the differences and/or similarities between the structures of L1 and L2 on the target language through interview and giving task process. It was conducted as classroom activities because it took a place in the classroom. The conclusion of this study was that the L2 structures produced by the learners were influenced by their L1 caused by the lack of the L2 and L1 knowledge. Meanwhile, in the present study, it is focused on the language varieties existing in Al-Amanah Islamic Modern College seen from language in contact. Seen from the title, this study does not only discuss about linguistic interferences but each linguistic aspect which becomes the results of language contact. In this case, the language varieties are uttered not written or read. The utterances are in the levels of phonemes, phrases, and sentences. In addition, this study was conducted to know the phenomena of language varieties existing in Al-Amanah Islamic Modern College in which the data obtained from the students’ utterances and analyzed by using Miles’ and Huberman’s data analysis model including data reduction, data display, and conclusion and verification. In addition, the application of the use of sociolinguistics point of view and the study is not only in the classroom but also out of it, is applied in this study. In summary, language varieties happening in Al-Amanah Islamic Modern College is English influenced by Surabaya and Sidoarjo Javanese caused by some factors, and these language varieties are unacceptable in language speakers’ society. There is something unique in this Al-Amanah Islamic Modern College. It is the language varieties the students use. The language varieties used by the students are totally different from the language varieties used by most of people in some regions. They create some new words from a language, but the real words of the language still appear. Not only creating some new words but, they also create a specific language structure and tone based on their regional language while they are speaking. Therefore, this study is written to know the phenomena of language varieties existing in Al-Amanah Islamic Modern College, krian, Sidoarjo. Research Questions Based on the study focus elaborated in the background of study above, the reach questions should be answered are: How are the language varieties in Al-Amanah Islamic Modern College, Krian seen from language in contact? Why do the students of Al-Amanah Islamic Modern College use those kinds of language varieties? To what extent can the students’ language varieties be accepted in the English speakers’ society? Purposes of the Study To describe the language varieties of Al-Amanah Islamic Modern College students seen from language in contact. To know why the students of Al-Amanah Islamic Modern College use those kinds of language varieties. To know to what extent the students’ language varieties can be accepted in the English speakers’ society. RESEARCH METHOD In conducting the study, the descriptive qualitative method is applied. The purpose of using the descriptive qualitative method is to obtain systematical description and accurate data which are dynamic, complex, and need very deep understanding. The subjects and the location of this study were the students of Al-Amanah Islamic Modern College, Krian, Sidoarjo who were taken randomly. It was done to obtain the more accurate and avoid data manipulation. The students of Al-Amanah Islamic Modern College were chosen because they are required to be able to communicate in foreign languages. Besides the students, foreigners from Russia, Brazil, United State of America, and Australia also became the subjects of this study who are used to answer the third research question. The location must be in Al-Amanah Islamic Modern College. The data of this study are classified into three types. They are linguistics, information, and assessments. The linguistics data are the language varieties which were uttered by the students of Al-Amanah Islamic Modern College. Secondly, information as data means that the data which are needed are related to the language varieties. They cover the reasons why the students produce them, the number of Al-Amanah Islamic Modern College students, and the year when English began to be spoken. Meanwhile, the sources of data are grouped into three types. They are people, places, and papers. In this study, the people were the Al-Amanah Islamic Modern College students who were taken randomly, an alumnus and English teacher, and some foreigners from different countries who know English. The foreigners were used to measure whether their English is acceptable or not. Secondly, the place is in Al-Amanah Islamic Modern College. Thirdly, the papers as sources, in this case, mean that the data are obtained from the related theories both from the books and internet and from the college documents (Arikunto in Afidah, 2009: 27). There are four techniques which were applied. They were observation, interview, and questionnaire, and assessments by an English teacher and four foreigners. The type of the observation which was used was participative active observation. Participative means that the researcher enjoys getting along with the respondents in the Islamic college. Active means that the researcher enjoys doing what the respondents do there, but it is not complete enough (Sugiyono, 2010: 310). The type of the interview which was used was semi-structured interview. They were twelve students of 12th grades who were taken randomly including the chief of the language division both boy and girl. They were chosen because they have been living in this college longer than the other students in the other grades. Besides using those two data collection techniques, the questionnaire was also used to obtain the data. This was conducted to know the language varieties in the levels of phonemes, phrases, and sentences. Meanwhile, the respondents of conducting questionnaire were taken randomly. They were two students of 9th grade, 11th grade, four students of 8th grade, 10th, and five students of 12th grades. The data were obtained by conducting assessments process which was assessed by an English teacher of Al-Amanah Islamic Modern College and foreigners. The process was that they were sent the assessments sheets, and some records which consisted of the students’ conversations using their language varieties through social networks namely Skype, and Facebook. The assessments sheet was based on the Likert scales model. According to Tullis and William (2013: 123), the Likert scales were used to know the acceptability of language through some scales such as “acceptable” or “not acceptable”. Meanwhile, the voices which were recorded were the voices of two boy students of 12th grade, and two girl students of 12th grade. Besides, the foreigners were four foreigners who come from Russia, Brazil, United State of America, and Australia. There were some instruments which were used. They were the researcher, interview sheets, questionnaires, and assessments sheets. The final part of research methods was data analysis. It presents some steps how to analyze the data. In this case, Miles’ and Huberman’s (1994: 10-12) data analysis model was applied. They wrote in their book that there are three steps to analyze the data. They are data reduction, data display, and conclusion and verification. RESULTS AND DISCUSSIONS 1. Language Varieties Phenomena Seen from Language in Contact The language varieties in Al-Amanah Islamic Modern College seen from language in contact are influenced by dialect, accent of Surabaya and Sidoarjo Javanese. The results are multilingualism, interferences, integration, code-switching and code-mixing, pidgin, and creole. To begin with, the dialect of the Al-Amanah Islamic Modern College students’ English is based on Surabaya and Sidoarjo dialect. It can be proved when the students are producing words in the interrogative sentence such as “tak-en”, “call-en”, “strik-en”, etc. (Instead of take, call, strike, etc.). The“-en” morpheme usually appears in Surabaya and Sidoarjo Javanese. In the standard Surabaya and Sidoarjo Javanese words, they should be “jukuen”, “celuken”, “kaploken”, etc. In addition, Dialect is a language variation from a group of speakers with certain numbers and region (Chaer and Leonie, 1995: 83). Besides Javanese with Surabaya and Sidoarjo dialect, the English of Al-Amanah Islamic Modern College students are also influenced by Surabaya and Sidoarjo Javanese accent. Accent is the way to pronounce a language with certain stress that can identify where the speakers live, their ethnicity, their first language, and so on (Lippi-Green, 1997: 83). Based on where the speakers live, most of them live in Sidoarjo and its surroundings. Besides, most of the students’ ethnicity is Javanese and with Javanese considered as their first language exactly. The existence of language contact may have consequences. The consequences are that there are some other language phenomena which are caused by language contact. According to Chaer and Leonie (1995: 111-187), Hall (in Odimengwu, 2012: 6), and Thomason (2001: 157), the phenomena are bilingualism and multilingualism, diglossia, interference, integration, code-switching and code-mixing, pidgin, creole, and language shift. However, Al-Amanah Islamic Modern College has only some phenomena, they are, multilingualism, interferences, integration, code-switching and code-mixing, pidgin, creole, and language shift which are explained as follows. Multilingualism The students of Al-Amanah Islamic Mocdern College are a multilingual community. They live together in a place and can speak in more than two languages. The speaker who can speak in more than two languages is called as multilingual (Fromkin, et al., 2011: 41; Tucker, 1999). Interferences According to Liliweri (2007: 159), interference is divided into phonological interference, morphological interference, syntactical interference, and semantic interference. However, in Al-Amanah Islamic Modern College, there are only three types of interferences which have been found. They are phonological interference, morphological interference, and syntactical interference. However, the name of those interfered or mixed languages which arise in a contact situation can be named as pidgin. To begin with, the English words begin with /v/ sound is changed to be /f/ such as in the word “very /?veri/” which is pronounced as “fery /?feri/”. Besides, the /ð/ sound is changed into a pure /d/ sound and sometimes with nasalization process. The examples are “the /nd?/ or /d?/”, “this /nd?s/ or /d?s/”, “that /ndæt/ or /dæt/”, “these /ndi?s/ or /di?s/”, and “those /ndo?s/ or /ndo?s/”. The pure /d/ sounds happen because Surabaya and Sidoarjo Javanese do not have /ð/ sound. This is line with Rochmawati’s (2007: vii) thesis which stated that there were some difficult consonants to pronounce. They were /v/, /?/, and /ð/ which are caused by the absence of those sounds in Indonesian. Besides, the /d/ sound with nasalization process occurs because Surabaya and Sidoarjo Javanese dialect usually add /n/ sound before the /d/ sound. This is as what Liliweri (2007: 159) explained that the Javanese usually pronounce the words begin with /b/, /d/, /g/, /j/ with some nasalization processes. However, the /b/, /g/, /j/ sounds are still able to be pronounced well by the students of Al-Amanah Islamic Modern College. Morphological interference is the use of affixes which are taken from another language (Weinreich, 1979: 68). This can be seen from the English words of Al-Amanah Islamic Modern College students which were influenced by Surabaya and Sidoarjo Javanese such as “eat-en”, “call-en”, “borrow-o”, “go-o”, “di-call”, and “di-visit-i”, etc. In fact, the affixes “-en”, “-o”, “di-”, and “-i” commonly appear in Surabaya and Sidoarjo Javanese which mean order (-en, -o), and passive (di-, and di- -i). Meanwhile, the syntactical interference in Al-Amanah Modern College can be seen when a structure of another language is applied to construct the language which is spoken. In this case, another language means Javanese while spoken language is English. Something should be noticed that Javanese has quite similar structure as English, that is, “S-V-O”. This is as what Bhela and Weinreich (1999: 28; 1979: 37) said that the L2 learners tended to use their L1 to construct their L2. The examples are as what had given before. Integration The word which was found in Al-Amanah Islamic College which is related to the example of integration is “Sarong” such as in the students’ utterance “Don’t ghasab my sarong!”. Sarong is actually comes from Javanese. Then, it is adopted by English and it is used as its own language. In order to know whether the word was adopted or was not being adopted yet is by looking up the dictionary. Nowadays, the word “sarong” is available in the English dictionary. It shows that the word “sarong” was considered as the part of English. In the other hand, “ghasab” is actually neither English nor Javanese. It is written in italic font because it is from another language namely Arabic. In short, a language can be called as integration when a language is adopted by another language and is used in the recipient one as its own (Yule, 2010: 54). Code-Switching and Code-Mixing Code-mixing often happen in the bilingual and multilingual community. It is like what usually happens in Al-Amanah Islamic Modern College. The example is like in the given conversation. AO : “Hee! Arak-arek nang ndi?” (“Hey, where are the others?”) LB : “Mbuh, nang ndi maeng. Budhal dhisek padalan maeng.” (“I don’t know. They went to school though.”) English teacher : “Where is RF?” Ok & LB : “Don’t know, Mr.” In the example above, AO and LB were making conversation. However, they did not use only one language. They switched their languages from Javanese to English in the complete sentences. The Javanese is shown by the fonts which are written in italic. The phenomenon of switching a language to another in the complete sentences in the same time and in the one conversation is named as code-switching (Troike in Wahyuningtyas, 2009: 14). Meanwhile, because they were speaking in Javanese and switching into English, the kind of code-switching is named as external code-switching which external code-switching is the switching of mother tongue to the foreign language (Hymes in Rahardi, 2001: 20). Code-mixing also commonly happens in their conversation. Code-mixing happens when a speaker mixes one language with another within a sentence. In this sense, Al-Amanah Islamic Modern College students mixed their English with Javanese in sentences. The Javanese are written in italic fonts. The conversation can be seen as follows. M : “This ball loh big-e.” (“This ball is so big.”) U : “Sing where? Sing on the mosque ta?” (“Which ball? Is the ball which is on the mosque?”) This brief conversation refers to code-mixing phenomena because it consists of the mixture of English and Javanese within a sentence. The Javanese is shown with the italic writing. Ping (2008: 4) said that code-mixing is the embedding of various linguistic units such as affixes (bound morphemes), or words (unbound morphemes), phrases and clauses from a cooperative activity where the participant, in order to infer what is intended, must reconcile what they hear with what they understand. Convergence The students of Al-Amanah Islamic Modern College have different capacity. Capacity means that they have different understandable and ability in mastering English. Although they have different capacity, they use English which is influenced by Surabaya and Sidoarjo Javanese and accent rather than the other types of languages in their communication. This process is called convergence (Chaer and Leonie, 1995: 171). Pidgin and Creole The language varieties in Al-Amanah Islamic Modern College are in contact. They are English which is in contact with Javanese. English is influenced by the Javanese. These language varieties are also used for certain purpose, that is, study. Besides, these mixed languages create a new language variety, and do not have any native speakers. However, there are still the senses of the English and the Javanese. The appropriate name of this language variety is pidgin. It is due to the fact that this language variety is a mixed language, used for certain purpose, and do not have any native speakers (Hall in Odimegwu, 2012: 6). Creole is the opposite of pidgin. Pidgin does not have a native language speaker like creole. Meanwhile, creole is a pidgin which is used as a mother tongue (Kushartanti, et al., 2005: 62). It is clear that the English of Al-Amanah nowadays is named as creole rather than pidgin. It is due to the fact that the speakers of pidgin were not there anymore. In constructing the formation of English, the students commonly tend to use Javanese which becomes the students’ first language. This is supported by Bhela’s (1999: 28) study which stated that the structure of the second language is constructed based on the students’ first language. Meanwhile, D’Souza (in Sumdangdej, 2007: 9) argues that there are three processes of interlanguage formation. They are including language transfer, overgeneralization, and simplification. Language Shift Language shift concerns with the use of language by a speaker or a group of speakers caused by migration from one speech community to another (Chaer and Leonie, 1995:187). The students of Al-Amanah Islamic Modern College move from a place to another. The place is from where they are from to Al-Amanah Islamic Modern College. It is due to the fact that Al-Amanah Islamic Modern College obliged the students to speak in English, they must put their ethnic languages away. However, if the Islamic college does not oblige the students to use English, the phenomenon of language shift never occurs. 2. The Factors of the Language Varieties Existence Multilingualism: Javanese as the Majority Language contact happens because of bilingualism and or multilingualism (Thomason, 2001: 1). The students of Al-Amanah Islamic Modern College are the real example of multilingual speakers. They can speak in their own ethnic languages, Indonesian, English, Arabic, and refined Javanese. However, when they create English, the structures of their languages are based on the structures of Surabaya and Sidoarjo Javanese. Lack of Vocabularies and Grammar Knowledge There are two problems which cause the existence of language varieties in Al-Amanah Islamic Modern College. They are lack of vocabularies and lack of English grammar knowledge. The lack of vocabularies can cause a code-mixing phenomenon. It mixes between English and Javanese. Meanwhile, a code-mixing is a kind of language varieties seen from language in contact. It is supported by Mecham’s and Janie’s (in O'Grady, 2001: 537-590); Chaer’s and Agustina’s (2010:84); Hall’s (in Odimengwu, 2012: 6); Thomason’s (2001: 157) statements stating that language variety is a variation of using language including dialect, accent, and other linguistic variations such as language in contact phenomena. The lack of grammar knowledge also becomes problem for the students of Al-Amanah Islamic Modern College. The respondent 28, 12th grade of Al-Amanah Islamic Modern College students explained that the lack of grammar knowledge still becomes the students’ serious problem. Most of us still do not know how to make a correct sentence.” It can be proved when the students construct some types of sentences. In the past situation, they do not use simple past of other grammar rules related to the past action. Besides, to make passive voice, some of them add affix “di-”, such as in “Mr. Toni di-call Mr. Rohim and some of them add “to”, such as in Mr. toni to call with Mr. Rohim. In fact, those should be Mr. Toni is called by Mr. Rohim. Last but not least, this is in tone with Bhela (1999: 31) stating that the reason why the students get interference is because of lack of grammar knowledge. Cultural Heritage of the Senior Students One of the results of language contact is pidgin and creole. Those two languages show clearly about the relation among a generation to another. In this sense, the seniors bequeath the language varieties which become the result of language in contact. Thomason (2001: 19) said that language contact is one of the results of the annual languages. Unfortunately, the English which was bequeathed was not the standard one. The existence of the cultural heritage of the senior students has positive and negative effects. The positive effect of the cultural heritage is that the students have great confidence to speak in English. It means that it can encourage the students to speak in English without feeling shy of making mistake. They can enjoy speaking in English although the language that they use is not as the standard one. Most of the students who became the respondents stated that they were happy except the chiefs of the language divisions. They were happy because they had identity, that is, English of Al-Amanah Islamic Modern College which totally different from others. However, both chiefs were not happy because they felt that it was not good. It sounded strange and different from the standard one. In contrast, the difference from the standard one is one of the negative effects. However, it is unacceptable. This fact gives the English teacher a certain sense. He seemed disappointed when he heard that Al-Amanah Islamic Modern College English is unacceptable. Habit Habit in the use of the improper English also becomes one of the factors of the language varieties existence in Al-Amanah Islamic Modern College. The students do not have a habit in producing the good English while speaking. In the other words, they can be said that they are lack of practicing in the use of the proper English. The respondent 16, as the chief of the boy language division, and the respondent 28, as the chief of the girl language division said that they felt less in practicing the English correctly and often produced the English as what is going on now even though they do not actually feel happy. These statements are in tone with Rochmawati’s thesis (2007: 53) stating that the students of Al-Furqon Muslims Boarding School have trouble of interference which it is because of lack of practice. Meanwhile, language is an arbitrary system which is used conventionally and used as a habit. The language varieties in Al-Amanah Islamic Modern College are the combination between English and Surabaya and Sidoarjo Javanese. However, those are created based the agreement and acceptability among the students. There are no students who do not understand the language varieties that they create. All of them agreed and accept for their daily communication so that they can work together. This phenomenon has happened for a long time. Besides, this becomes the students’ habit in the use of English with the combination of Surabaya and Sidoarjo Javanese. There are only very few students who try to speak in the proper English. They are the students with special capacity. However, they sometimes still use the language varieties that commonly used by the other students. Therefore language is called as an arbitrary system which is used for daily communication and showing education level (Chaer 1994:45; Evans and Stephen, 2009: 429-492). The Islamic College Rules To begin with, the rules that have been created by this Islamic College in the use of language are that the students must speak in English in certain time and without any forces to speak in the proper English. This must be underlined that there are no any demands in the use of the proper English. This is emphasized by respondent 15, one of the 12th grade students of Al-Amanah Islamic Modern College stating, “We are not sued to speak in a good English syntactically and grammatically but, we are only sued to be able to speak in English.” In addition, this is also supported by the Tujuh Kewajiban Santri (Students’ Seven Obligation) which is written that the students of Al-Amanah Islamic Modern College must speak in the official languages. They are English and Arabic. However, Javanese is not written because this Islamic college is popular with the bilingualism, English and Arabic. Therefore, this Islamic College is named as Al-Amanah Islamic Modern College because this Islamic does not teach the students only the Islamic studies (Turmudi, 2004: 45). Meanwhile, the use of refined Javanese is only uttered by the Islamic priest of this Islamic College and it is used on Sunday. 3. The Language Varieties Acceptability Based on the Four Foreigners The assessments by the four foreigners who come from different countries stated that the language varieties of the students of Al-Amanah Islamic Modern College are unacceptable. In the other words, it can be stated that English which is influenced by the dialect and the accent of an ethnic language cannot be understood. According to Chomsky (in Jacobsen, 1992: 10); Chomsky (2002: 15), there are some possibilities relations between grammaticality and acceptability. The possibilities relations can be seen as follows. 1) Grammatical and acceptable sentence. (+Grammatical, +Acceptable) It happens when the syntactical structure of a sentence is correct and makes sense. The example is “I read my books every day”. 2) Ungrammatical and unacceptable sentence (–Grammatical, –Acceptable) It happens when the syntactical structure of a sentence is incorrect and automatically does not make sense. In addition, “grammaticality is a prerequisite for acceptability” (James in Wetzorke, 2005: 14). The example is “books my read I every day”. Another example is like when the ungrammatical language varieties of Al-Amanah Islamic Modern College students cannot be understood by the foreigners. 3) Grammatical and unacceptable sentence (+Grammatical, – Acceptable) When a sentence has a correct structure syntactically, however, it does not make any senses. It sometimes depends on the context. The example is “The flower whispers me”. It has correct English structure but the meaning is unacceptable because logically the sense is nonsense. It also can be acceptable when it is used in the literature field such as poem. So, the context is really important here. 4) Ungrammatical and acceptable sentence (–Grammatical, + Acceptable) If a sentence or an utterance syntactically is incorrect, it is called as ungrammatical. However, if it makes sense, it is considered as acceptable. It is like what is happen in the language varieties of Al-Amanah Islamic Modern College students. The example is “I have done di-take-no with Oktav”. The language varieties in Al-Amanah Islamic Modern College are obviously ungrammatical. However, it can be accepted by the students of Al-Amanah Islamic Modern College. In conclusion, the language varieties which are considered acceptable in Al-Amanah Islamic Modern College, in fact, are unacceptable for the foreigners. Indeed, acceptability is really concerning with the speakers’ and the interlocutors’ competency. However, the barometer of the acceptability of English in this study is the foreigners. If the foreigners can understand it, it means that the English of Al-Amanah Islamic Modern College can be used in international. CONCLUSIONS AND SUGGESTIONS Conclusions From the discussion explained in the previous chapter, it can be concluded that there are many language varieties phenomena in Al-Amanah Islamic Modern College seen from language in contact. The languages which are in contacts are English and Javanese. The language varieties are in the forms of dialects, accents, and other linguistic varieties. The dialects and accents existing are English influenced by Javanese with Surabaya and Sidoarjo dialects and accents. Meanwhile, the other linguistic varieties found in Al-Amnah Islamic Modern College are multilingualism, interferences, integrations, code-switching and code-mixing, pidgin, and creole. Those never happen if there are no certain factors can cause them. There are some factors which cause the existences of language varieties in Al-Amanah Islamic Modern College seen from language in contact. Firstly, it is multilingualism which is specialized for Javanese as the majority language which can dominate the minority one. Secondly, the lack of vocabularies and grammar knowledge which are experienced by the Al-Amanah Islamic Modern College students also become the reasons of the existence of the language varieties. thirdly, the existence of the seniors’ heritage which shows that the existence of language varieties in Al-Amanah Islamic Modern College seen from language in contact is started by the senior students then continued by the junior ones. Fourthly, habit is also included into one of the factors in which the habit of speaking Javanese can influence the way they speak in English. Last but not least, the role of Islamic college also becomes the factor stating that students are not sued to speak in the Standard English, however, the important one is that they can speak in English no matter whether their English is influenced by the Javanese or not. To know whether the students’ language varieties are acceptable or not, here, there are four assessments which were done by foreigners who comes from Russia, Brazil, United States of America, and Australia. They stated that those language varieties are unacceptable. It means that those language varieties cannot be understood. Although there are some words can be got, however, they are only the English words not the English words which are influenced by Surabaya and Sidoarjo Javanese. However, Al-Amanah Islamic Modern College and the English teacher still can understand it well. It is due to the fact that the barometer is the foreigners, thus, the appropriate answer is that those language varieties are unacceptable. Suggestions As an institution orienting on English as the foreign language for daily communication, Al-Amanah Islamic Modern College should improve the system to be better, especially for the use of English. It can be the rule stating that the students must be able to speak in correct English rather than only to speak in English no matter whether it is correct or not. It is due to the fact that the study shows that the English of Al-Amanah Islamic Modern College students are unacceptable in the English speakers’ society. For the teachers, the teachers should teach the students harder and harder. It is due to the fact that most of the students do not know how to construct a good sentence in English. If they still do not know how to construct a good sentence, the error language will always occur among them. In fact, there will never standard English can be used to communicate in the international. Language division also has a crucial role in controlling the students’ language in Al-Amanah Islamic Modern College. The language division should master the English better than the majority students who are not the member of the division. They should be able to be good figure in producing the English concerning with the vocabularies, grammar, and the way to pronounce the English. The students of Al-Amanah Islamic Modern College should be more serious in learning the English. They have to practice it more and more in their daily conversation. Yet, it is not only practice it but, it must be practiced as well. So that, they can learn the language better which can be acceptable in the English speaker’s society. Last not least, this study is far away from the perfection. Therefore, the next researchers are hoped to conduct the research related to unacceptable ones including the factors that make those kinds of language varieties unacceptable. It is hoped that what is not found yet can be found and can be closer to the perfection. REFRENCES Afidah, Nurul. (2009). ‘Standard of Javanese politeness: ‘The use of Javanese Speech Levels by Islamic Preaches’. Unpublished Thesis S-1 of State University of Surabaya. Bhela, Baljit. (1999). ‘Native Language Interference in Learning a second Language: Exploratory Case Studies of Native Language Interference with Target Language Usage’. International Education Journal 1(1), 22-31. Chaer, Abdul and Leonie Agustina. (1995). Sosiolinguistik Perkenalan Awal. Jakarta: Rineka Cipta. Chomsky, Noam. (2002). Syntactic Structures. The Hague: Mouton. Evans, Nicholas and Stephen C. Levinson. (2009). ‘The Myth of Language Universal: Language Diversity and Its Importance for Cognitive Science’. Behavioral and Brain Sciences 5 (32), 429-432. Fromkin et al. (2001). Introduction to Language Ninth Edition. New York: Wadsworth. García, Ofelia and Colin. (1995). Policy and Practice in Bilingual Education: A Reader Extending the Foundations. Great Britain: WBC Ltd. Holmes, Janet. (2001). An Introduction to Sociolinguistics. UK: Longman. Jacobsen, Bent. (1992). Remarks on Acceptability and Grammaticality. [Online]. Available: (http://download2.hermes.asb.dk/archive/download/H08_01.pdf), [September 26, 2013]. Kushartanti et al. (2005). Pesona Bahasa langkah Awal Memahami Linguistik. Jakarta: PT. Sun Printing. Liliweri, Alo. 2007. Makna Budaya dalam Komunikasi Antarbudaya. Yogyakarta: Lkis Yogyakarta. Lippi-Green, R. (1997). English with an Accent: Language, Ideology, and Discrimination in the United States. New York: Routledge. Moesa, Ali Maschan. (2007). Nasionalisme Kiai Konstruksi Sosial Berbasis Sosial. Yogyakarta: LKiSYogyakarta. Miles, Matthew B. and A. Michael Huberman. (1994). Qualitative Data Analysis: An Expanded Sourcebook Second Edition. California: Sage Publication, Inc. Odimegwu, Pamela. (2012). A Comparative Analysis of Jamaican Creole and Nigerian Pidgin English. Nigeria: Internetpages & Webdesign. O'Grady, William et al. (2011). Contemporary Linguistics. Boston: Bedford. Ping Liu. (2008). Code-Switching and Code-Mixing. Paper Presented in the Subject English Language and Literature Studies - Linguistics. University of Stuttgart nd 2008. Rachmawati, Nur Sichah Atik. (2007).’The Interference of Bahasa Indonesia to The Production of English Sounds Made by The Third Grade Students of Junior High School in Al-Furqon Muslim Boarding School’. Unpublished Thesis S-1 of State University of Surabaya. Rahardi, R. Kunjana. (2006). Dimensi-Dimensi Kebahasaan: Aneka Masalah Bahasa Indonesia Terkini. Jakarta: Penerbit Erlangga. Sugiyono. (2010). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Alfabeta, CV. Sumdangdej, Suthee. (2007). Input and The Acquisition of Suprasegmental Phonology in English by Thai School Children. [Online], Available: (http://etheses.dur.ac.uk/2479/), [September 19, 2013]. Thomason, Sarah Grey. (2001). Language Contact. Edinburgh: Edinburgh University Press. Tucker, G. Richard. (1999). A global Perspective on Bilingualism and Bilingual Education. [Online], Available at Durham E-Theses: (http://www.cal.org/resources/Digest/digestglobal.html), [September 12, 2013]. Tullis, Thomas and William Albert. (2013). Measuring the User Experience: Collecting, Analyzing, and Presenting Usability Metrics. Waltham: Elsevier Inc. Turmudi, Endang. (2004). Perselingkuhan Kiai dan Kekuasaan. Depok: PT LKiS Pelangi Aksara. Wahyuningtyas R., Noor. (2009). ‘The Study of Code-Switching in Movie Mr. Bean’s Holiday’. Unpublished Thesis S-1 of State University of Surabaya. Weinreich, Uriel. (1979). Languages in Contact. New York: Mouton Publisher. Wetzorke, Robert. (2010). An Introduction to the Concepts of Error Analysis. Paper Presented in the subject English - Pedagogy, Didactics, Literature Studies. Technical University of Braunschweig nd 2010. Yule, George. (2010). The Study of Language 4th edition. New York: Cambridge University Press.